Comparative Analysis of the Capabilities of IPv6 and IPv4 Protocols to Provide the Designated Quality of Service - V. V. Bachilo; V. I. Dravitsa; N. I. Listopad (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2023)
The paper presents a comparative analysis of the IPv4 and IPv6 data transfer protocols to ensure a given quality of service (QoS). As parameters of QoS, the bandwidth and the associated transmission rate, as well as the amount of delay and jitter – delay variations are analyzed. The main disadvantages and advantages of both protocols are presented in the form of a table. A model of real interaction between networks operating on the basis of IPv4 and IPv6 protocols has been developed and implemented. The throughput, delay and jitter were measured for an IPv4-based network and an IPv6-based network for various packet sizes (MTU) for UDP and TCP traffic. Conclusions are drawn concerning the possibility and prospects for using the IPv6 protocol to provide a given quality of service.